Benchmarking operations management education in the European Union - Silva, J.; Leandro, V. (Proceedings 21st EurOMA Conference, Operations management in an innovation economy, 2014)
This research aimed at strategically positioning a masters targeting Operations Managers education, by pursuing a benchmarking exercise within the EdUniversal ranking. The literature review identified different roles and required skills for Industrial Engineers and Operations Managers, while the empirical study justified the choice of the other programs to be compared, confirmed the adequateness of the ranking category and the Bologna influence. The resulting SWOT analysis suggested a growth strategy based on internationalization and networking, as well as adjustments to the selection, divulgation and contents. Strategy implementation already produced as results the upgrade to the 21rst position of the EdUniversal ranking.